If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -13 = -22 + -3x Solving -13 = -22 + -3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3x' to each side of the equation. -13 + 3x = -22 + -3x + 3x Combine like terms: -3x + 3x = 0 -13 + 3x = -22 + 0 -13 + 3x = -22 Add '13' to each side of the equation. -13 + 13 + 3x = -22 + 13 Combine like terms: -13 + 13 = 0 0 + 3x = -22 + 13 3x = -22 + 13 Combine like terms: -22 + 13 = -9 3x = -9 Divide each side by '3'. x = -3 Simplifying x = -3
| 5a-1=16.5 | | 32-5[4+3(2+1)-6]= | | 9y-3=19-y | | y=50+2.5x | | 2x+10+x+3(2x+10)-40=162 | | 7+16x-1-4x=24+8x-9+3x | | X-6.4=-2.6 | | 72+(a+b)=180 | | 3m^2-11m-6=0 | | 4k+11=-7(3k+1)-7 | | 10(x+3)+10=50 | | 2x+17-7x-6=8-10x-19+10x | | 4x-25=25 | | 10x-4x=40+8 | | 6y+8=2x | | 300x^2-507=0 | | 5*6+y=0*5+y | | v^2+13v+29=v-7 | | 11x-4-9x=21-3x | | .5x-6=-7 | | -10-7w=-4-6w | | 125=-.5x^2+25x-150 | | 2+9x=100 | | -49+10x-6x=43 | | -2.2+-8.9= | | x-4.5=12.01 | | h^2*j*k^3=343 | | 125(3x-2)=25(2x+1) | | 4p-8=4(p-2) | | 04x+3.9=5.78 | | 2(x+4)=2(x-1)+3 | | 13-6x=-5(x-4) |